ADAPTASI PSIKOLOGI SOSIAL ISTRI KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI KABUPATEN PATI (STUDI KUALITATIF PADA ISTRI KORBAN KDRT DI KABUPATEN PATI) - Fatma Zakiyya Amanullah; Kusyogo Cahyo; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In Indonesia, 2011 to 2015, cases of violence against women has increased every year. 2014 until July 2016, there were 15 cases domestic violence against the wife in Pati regency. Among the effects of domestic violence against his wife among other psychological effects and physical effects that cause various physical responses, psychological and social victims of domestic violence itself. The purpose of this study was todescribe social psychological adaptation wife of victims of domestic violence in Pati regency.This qualitative study used a descriptive approach. With purposive sampling techniques showed 6 research subjects who are wives of victims of domestic violence. The data collection was done by in-depth interviews to 6 subjects. Data validation is done by triangulation to 12 people.Results from the study showed that the practice of social psychology adaptation wife do victims of domestic violence arising from the interaction between the environment and cognitive victims. Lack of education about the form of domestic violence, a lot of verbal domestic violence victim's wife did not realize that the word rant receipt included in the violence, so consider fair if domestic squabble by using harsh words. It also affects the awareness of domestic violence victims to report verbally to the police. Society gossip wife to victims of domestic violence is still a culture in Pati regency. This opt out of society in reporting the domestic violence problem caused a perception that domestic violence is an internal matter of the family. Self-perception of domestic violence after the study subjects likely to lead to negative actions. Their strong motivation of the subject and its surroundings make the subject was able to regulate and control himself. Emotional support, informative, and appreciation of the family made the subject was able to interact well withfamily. Maintain contact with peers, being one of the alternatives to forget about the problems of domestic violence.